Cultural Collisions As Disorienting Dilemmas: Transformative Learning Through Authentic Intercultural Communication In Vietnamese EFL Education - Hoa Ngo Quynh; Tu Do Thanh (WISE Pendidikan Indonesia, 2026)
This study aims to examine the cultural disorienting dilemmas experienced by Vietnamese EFL students during authentic intercultural communication and to explore how such encounters reshape their meaning perspectives as English communicators. Grounded in Transformative Learning Theory, this qualitative study involved nine third-year English-major students who participated in an experiential EFL module requiring field interviews with foreign tourists. Data were collected through semi-structured interviews and analyzed thematically. The findings show that authentic intercultural encounters exposed learners to mismatches in communication styles, politeness norms, and interactional expectations, generating emotional responses such as shock, anxiety, and self-doubt that prompted critical reflection. Over time, these experiences contributed to greater cultural relativity, increased communicative confidence, and a reconfiguration of self-perception from evaluated learners to more legitimate English users. The study demonstrates that authentic intercultural communication can function not only as a site of language practice but also as a catalyst for transformative learning in locally situated EFL contexts. This study contributes to the literature by extending Transformative Learning Theory into Vietnamese EFL education and by highlighting the pedagogical significance of integrating authentic intercultural engagement into EFL curricula to foster intercultural awareness, reflective capacity, and communicative identity development.